A nickel-rich ternary single crystal positive electrode material and its preparation method and use

During the preparation process of high-nickel ternary cathode material, it is pre-entered and lithium supplemented by wet method to form a nickel-rich ternary single crystal cathode material, which solves the difficulty and stability of the material in the production process and improves the performance of the battery.

CN116354416BActive Publication Date: 2025-03-28SHANDONG AIA KESIMAO NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310377309.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-03-28
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

High-nickel ternary cathode materials have problems such as increasing difficulty, poor cycle stability and thermal stability in the production process, which limits their commercial application.

Method used

Using a preparation method of nickel-rich ternary single crystal positive electrode material, a single crystal material with a uniform surface morphology and an ordered layered structure is formed by pre-entrying into the lithium source on the nickel-rich precursor and wet lithium supplementation before secondary sintering.

Benefits of technology

The charging and discharging specific capacity of the battery, the first Coulomb efficiency and the circulation capacity retention rate are improved, and the circulation performance and thermal stability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116354416B_ABST
    Figure CN116354416B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a method for preparing a nickel-rich ternary single crystal positive electrode material, the method comprising: contacting and drying a mixed solution of sodium chloride, potassium chloride and a first lithium source with a nickel-rich precursor; mixing the nickel-rich precursor with a second lithium source and performing a first sintering to obtain a sintered material; after washing and drying the sintered material, supplementing lithium and performing a second sintering, after sintering, crushing and screening to obtain a nickel-rich ternary single crystal positive electrode material. The nickel-rich ternary single crystal positive electrode material prepared by the present disclosure has a uniform and smooth surface, and the layered structure on the surface of the material is more ordered, which effectively improves the battery charge and discharge specific capacity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of positive electrode materials for lithium-ion batteries, and in particular to a nickel-rich ternary single crystal positive electrode material and a preparation method and use thereof. Background Art

[0002] With the development of new energy vehicles, people have put forward higher requirements on the energy density, service life, rate performance, thermal stability and other properties of lithium-ion batteries. x Co y Mn z O2, 0.8≤x≤0.95, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1) has become one of the most promising and market-competitive lithium-ion battery cathode materials in the current power battery system due to its high energy density and low cost. The increase in nickel content has increased the specific capacity of high-nickel ternary materials, but it has also brought about problems such as increased difficulty in production process, poor cycle stability and thermal stability, which has seriously limited its commercial application. Summary of the invention

[0003] The purpose of the present invention is to provide a nickel-rich ternary single crystal positive electrode material and a preparation method and use thereof. The nickel-rich ternary single crystal positive electrode material prepared by the present invention has a uniform surface morphology and a smooth surface, and the layered structure on the surface of the material is more ordered, which effectively improves the battery's charge and discharge specific capacity, first coulomb efficiency and cycle capacity retention rate.

[0004] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a nickel-rich ternary single crystal positive electrode material, the method comprising:

[0005] (1) contacting a mixed solution of sodium chloride, potassium chloride and a first lithium source with a nickel-rich precursor and drying;

[0006] (2) mixing the nickel-rich precursor with a second lithium source and performing a first sintering to obtain a sintered material;

[0007] (3) After washing and drying, the sintered material is supplemented with lithium and subjected to a second sintering;

[0008] Wherein, the lithium replenishment method is wet lithium replenishment, the wet lithium replenishment uses an aqueous solution containing a third lithium source, the wet lithium replenishment method is performed by ball milling, and the ball milling time is 2 to 6 hours;

[0009] The usage of the third lithium source is 1000-6000 ppm relative to the mass of the sintered material.

[0010] Optionally, the usage of the third lithium source is 4000-6000 ppm.

[0011] Optionally, in step (1), relative to the mass of the nickel-rich precursor, the mass ratio of the nickel-rich precursor to the mixed solution is (2-8):1, preferably (2-6):1;

[0012] Among them, the mass ratio of sodium chloride, potassium chloride, the first lithium source and water in the mixed solution is (0.5-1.5): (0.5-1.5): 1: (0.5-1.5), preferably (0.9-1.2): (0.9-1.2): 1: (0.9-1.2).

[0013] Optionally, the molar ratio of the nickel-rich precursor to the total lithium source is (1.01-1.1):1, preferably (1.01-1.08):1;

[0014] Wherein, the total lithium source includes the first lithium source and the second lithium source;

[0015] The amount of the second lithium source is 85 to 95 parts by mole, preferably 90 to 95 parts by mole, relative to 100 parts by mole of the total lithium source;

[0016] The first lithium source is used in an amount of 5 to 15 mol parts, preferably 5 to 10 mol parts, relative to 100 mol parts of the total lithium source.

[0017] Optionally, the first sintering temperature is 450-600°C, preferably 500-550°C, and the holding time is 4-8h; the second sintering temperature is 810-860°C, and the holding time is 10-15h. The sintering is carried out in an oxygen atmosphere with an oxygen content of 90-100%.

[0018] Optionally, the method further comprises, after the second sintering is completed, crushing and screening, and the particle size D50 of the screened material is 1 to 1.8 μm.

[0019] The drying temperature in step (1) is 100 to 180° C. and the drying time is 2 to 6 hours;

[0020] In step (3), the washing method is to use ultrapure water at 5°C for washing according to the water-to-material ratio, the water-to-material ratio is (0.8-1.2):1, preferably 1:1, and the washing time is 8-10 minutes; the drying temperature is 100-150°C, and the time is 2-6 hours.

[0021] Optionally, the chemical formula of the nickel-rich precursor is as shown in formula (I): Ni x Co y Mn z (OH)2(I), wherein 0.8≤x≤0.95, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1.

[0022] Optionally, the first lithium source, the second lithium source and the third lithium source are the same or different and are selected from one or more of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate, lithium oxide and lithium nitrate.

[0023] The second aspect of the present disclosure provides a nickel-rich ternary single crystal positive electrode material prepared by the preparation method described in the first aspect of the present disclosure, wherein the chemical formula of the nickel-rich ternary single crystal positive electrode material is as shown in formula (II): LiNi x Co y Mn z O2(II), wherein 0.8≤x≤0.95, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1.

[0024] A third aspect of the present disclosure provides a lithium-ion battery comprising the nickel-rich ternary single crystal positive electrode material described in the second aspect of the present disclosure.

[0025] Through the above technical scheme, the preparation method provided by the present invention allows part of the lithium source to enter the surface and surface layer of the precursor in advance during the pretreatment of the nickel-rich precursor, thereby providing a driving force for the formation of a nickel-rich ternary single crystal material, and at the same time, it can make the single crystal material not easy to agglomerate during the sintering process, which is conducive to obtaining a better capacity retention rate; on the other hand, the preparation method provided by the present invention replenishes lithium by wet lithium replenishment before secondary sintering, which can make the lithium source more evenly attached to the surface of the material, more fully repair the defects on the surface of the material, make the surface of the material smoother, and the morphology more uniform, thereby improving the battery's charge and discharge specific capacity, first coulomb efficiency and cycle capacity retention rate.

[0026] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0028] Figure 1 This is a SEM image of the nickel-rich ternary single crystal positive electrode material prepared in Example 1 of the present disclosure. DETAILED DESCRIPTION

[0029] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0030] A first aspect of the present invention provides a method for preparing a nickel-rich ternary single crystal positive electrode material, the method comprising:

[0031] (1) contacting a mixed solution of sodium chloride, potassium chloride and a first lithium source with a nickel-rich precursor and drying;

[0032] (2) mixing the nickel-rich precursor with a second lithium source and performing a first sintering to obtain a sintered material;

[0033] (3) After washing and drying, the sintered material is supplemented with lithium and subjected to a second sintering;

[0034] The preparation method provided by the present disclosure provides a driving force for forming a high-nickel ternary single crystal material by allowing part of the lithium source to enter the surface and surface layer of the precursor in advance during the pretreatment of the nickel-rich precursor. In addition, lithium replenishment is performed by wet lithium replenishment before secondary sintering, so that the lithium source can be more evenly attached to the surface of the material, and the defects on the surface of the material can be more fully repaired, making the surface of the material smoother and the morphology more uniform, thereby improving the battery's charge and discharge specific capacity, first coulomb efficiency and cycle capacity retention rate.

[0035] In a specific embodiment of the present disclosure, the lithium replenishment method is wet lithium replenishment, the wet lithium replenishment uses an aqueous solution containing a third lithium source, the wet lithium replenishment method is carried out by ball milling, the ball milling time is 2 to 6 hours, preferably 2 to 4 hours; relative to the mass of the sintered material, the amount of the third lithium source is 1000 to 6000 ppm, preferably 4000 to 6000 ppm, more preferably 4000 to 5000 ppm. In the above embodiment, lithium replenishment by wet lithium replenishment before secondary sintering can make the lithium source more evenly attached to the surface of the material, more fully repair the defects on the surface of the material, effectively improve the battery efficiency and energy density, and improve the cycle performance.

[0036] In a specific embodiment of the present disclosure, in step (1), relative to the mass of the nickel-rich precursor, the mass ratio of the nickel-rich precursor to the mixed solution is (2-8):1, preferably (2-6):1, and more preferably (2-5):1;

[0037] In a specific embodiment of the present disclosure, the mass ratio of sodium chloride, potassium chloride, the first lithium source and water in the mixed solution is (0.5-1.5): (0.5-1.5): 1: (0.5-1.5), preferably (0.9-1.2): (0.9-1.2): 1: (0.9-1.2), more preferably 1: 1: 1: 7.5. In the above embodiment, by selecting the preferred ratio of raw materials for reaction, it is beneficial to improve the performance of the nickel-rich ternary single crystal positive electrode material.

[0038] In a specific embodiment of the present disclosure, the molar ratio of the nickel-rich precursor to the total lithium source is (1.01-1.1):1, preferably (1.01-1.08):1, and more preferably (1.01-1.05):1;

[0039] Wherein, the total lithium source includes the first lithium source and the second lithium source;

[0040] Relative to 100 molar parts of the total lithium source, the amount of the second lithium source is 85 to 95 molar parts, preferably 90 to 95 molar parts, and more preferably 92 to 95 molar parts; relative to 100 molar parts of the total lithium source, the amount of the first lithium source is 5 to 15 molar parts, preferably 5 to 10 molar parts, and more preferably 5 to 8 molar parts. In the above embodiment, by pretreating the nickel-rich precursor with a lithium source twice, the lithium source can pre-contact the surface of the nickel-rich precursor and enter the surface structure of the precursor, providing a driving force for the formation of a high-nickel ternary single crystal material.

[0041] In a specific embodiment of the present disclosure, the temperature of the first sintering is 450-600°C, preferably 500-550°C, and the holding time is 4-8h, preferably 4-6h; the temperature of the second sintering is 810-860°C, preferably 810-850°C, and the holding time is 10-15h, preferably 10-13h; the sintering is carried out in an oxygen atmosphere, and the oxygen content is 90-100%, preferably 98-100%. In the above embodiment, by selecting the preferred segmented sintering, the lithium source can be continuously diffused into the nickel-rich precursor to form a thermodynamically relatively stable nickel-rich lithium-ion positive electrode material, thereby improving the cycle performance and rate performance of the nickel-rich lithium-ion positive electrode material.

[0042] In a specific embodiment of the present disclosure, the method further comprises, after the second sintering is completed, crushing and screening, and the particle size D50 of the screened material is 1 to 1.8 μm, preferably 1 to 1.5 μm. In the above embodiment, by selecting the preferred crushing and screening operation, it is beneficial to disperse the agglomerated material after sintering.

[0043] In a specific embodiment of the present disclosure, the drying temperature in step (1) is 100 to 180° C., preferably 100 to 150° C., and the drying time is 2 to 6 hours, preferably 3 to 5 hours;

[0044] In a specific embodiment of the present disclosure, in step (3), the washing method is to use ultrapure water at 5°C for washing according to the water-to-material ratio, the water-to-material ratio is (0.8-1.2):1, preferably 1:1, and the washing time is 8-10 min, preferably 8 min; the drying temperature is 100-150°C, preferably 100-130°C, and the time is 2-6 h, preferably 3-5 h.

[0045] In a specific embodiment of the present disclosure, the chemical formula of the nickel-rich precursor is as shown in formula (I): Ni x Co y Mn z (OH)2(I), wherein 0.8≤x≤0.95, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1.

[0046] In a specific embodiment of the present disclosure, the first lithium source, the second lithium source and the third lithium source are the same or different and are selected from one or more of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate, lithium oxide and lithium nitrate, preferably lithium hydroxide monohydrate and anhydrous lithium hydroxide.

[0047] The second aspect of the present disclosure provides a nickel-rich ternary single crystal positive electrode material prepared by the preparation method described in the first aspect of the present disclosure, wherein the chemical formula of the nickel-rich ternary single crystal positive electrode material is as shown in formula (II): LiNi x Co y Mn z O2(II), wherein 0.8≤x≤0.95, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1.

[0048] The nickel-rich ternary single crystal positive electrode material prepared in the present invention has a uniform and smooth surface morphology, and the layered structure on the surface of the material is more ordered, which effectively improves the battery's charge and discharge specific capacity, first coulomb efficiency and cycle capacity retention rate.

[0049] A third aspect of the present disclosure provides a lithium-ion battery comprising the nickel-rich ternary single crystal positive electrode material described in the second aspect of the present disclosure.

[0050] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.

[0051] In the following examples and comparative examples, unless otherwise specified, the raw materials used are commercially available products.

[0052] Example 1

[0053] a. Prepare a mixed solution of sodium chloride, potassium chloride, lithium hydroxide monohydrate with 160 g ultrapure water in a mass ratio of 1:1:1, and evenly spray the mixed solution on 600 g of nickel-rich precursor (chemical formula: Ni 0.9 Co 0.05 Mn 0.05 The precursor was thoroughly mixed in (OH)2) and dried in a vacuum oven for 4 h at a drying temperature of 150°C.

[0054] b. According to the lithium ratio of 1.015, the remaining lithium hydroxide monohydrate is mixed evenly with the precursor dried in step a. Among them, the molar proportion of lithium hydroxide monohydrate in step a is 5 molar parts. Sintering is carried out in a box furnace and the temperature is raised to 550°C, and the heat preservation time is 6 hours. The temperature is raised to 550°C at 5°C per minute, and the temperature is kept for 6 hours, and then naturally cooled to room temperature to obtain a sintered material.

[0055] c. Mechanically crush the sintered material in step b, and wash it with water using a suction filtration device. The ultrapure water temperature is 5° C., the water-to-material ratio is 1:1, the washing time is 8 minutes, and the washing is performed twice.

[0056] d. The material in step c is dried in a vacuum oven for 4 hours at a drying temperature of 150°C. According to the mass of the sintered material in step b, the material is supplemented with lithium twice, the amount of lithium hydroxide monohydrate is 4500ppm, the lithium supplementation method is ball milling, and the ball milling time is 4 hours. The ball-milled material is sintered twice in a box furnace, the temperature is raised to 500°C, the heat preservation time is 3 hours, and then the temperature is raised to 760°C at 5°C per minute, and the heat preservation time is 6 hours.

[0057] e The secondary sintered material was taken out and crushed by air flow grinding. The air flow pressure was 5 MPa and the crushing particle size reached 1.3 μm to obtain a nickel-rich ternary single crystal positive electrode material.

[0058] Example 2

[0059] The method of Example 1 is adopted, except that the molar fraction of lithium hydroxide monohydrate in step a to the total lithium source is 20 molar parts.

[0060] Example 3

[0061] The method of Example 1 is adopted, except that in step d, the amount of lithium hydroxide monohydrate used is 3500 ppm.

[0062] Example 4

[0063] The method of Example 1 is adopted, except that, in step b, the sintering temperature is raised to 400°C in a box furnace, the holding time is 2 to 3 hours, the temperature is raised to 805°C at 5°C per minute, and the temperature is kept for 8 to 10 hours; in step d, the ball-milled material is subjected to secondary sintering in a box furnace, the temperature is raised to 350°C, the holding time is 2 to 3 hours, and then the temperature is raised to 600°C at 5°C per minute, and the holding time is 2 to 3 hours.

[0064] Example 5

[0065] The method of Example 1 is adopted, except that in step a, the chemical formula Ni 0.9 Co 0.05 Mn 0.05The nickel-rich precursor of (OH)2 is replaced by the same weight of Ni 0.92 Co 0.03 Mn 0.05 (OH)2.

[0066] Comparative Example 1

[0067] a According to the lithium ratio of 1.015, 600g of nickel-rich precursor (chemical formula Ni 0.9 Co 0.05 Mn 0.05 (OH)2) is mixed with lithium hydroxide monohydrate, and after being mixed evenly, the mixture is sintered in a box furnace and heated to 550°C for 4 hours, and then heated to 850°C at a rate of 5°C per minute for 10 hours, and then naturally cooled to room temperature to obtain a sintered material.

[0068] b. Mechanically crush the sintered material in step a, and wash it with water using a suction filtration device. The ultrapure water temperature is 5° C., the water-to-material ratio is 1:1, the washing time is 8 minutes, and the washing is performed twice.

[0069] c. The material in step b is dried in a vacuum oven for 4 hours at a drying temperature of 150°C. According to the mass of the sintered material in step a, the material is supplemented with lithium for a second time, the amount of lithium hydroxide monohydrate is 4500ppm, the lithium supplementation method is ball milling, and the ball milling time is 4 hours. The ball-milled material is sintered for a second time in a box furnace, the temperature is raised to 500°C, the insulation time is 3 hours, and then the temperature is raised to 550°C at 5°C per minute, and the insulation time is 6 hours.

[0070] d. The secondary sintered material is taken out and crushed by air flow grinding. The air flow pressure is 5 MPa and the crushing particle size reaches 1.3 μm to obtain a nickel-rich ternary single crystal positive electrode material.

[0071] Comparative Example 2

[0072] The method of Example 1 is adopted, except that in step d, no secondary lithium supplementation is performed.

[0073] Comparative Example 3

[0074] The method of Example 1 is adopted, except that in step d, the amount of lithium hydroxide monohydrate used is 6500 ppm.

[0075] Test Case

[0076] The materials of Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to electrochemical performance tests as follows:

[0077] The materials prepared in the examples and comparative examples were mixed with the conductive agent acetylene black and the binder PVDF in a mass ratio of 90:5:5, and then NMP (N-methyl-pyrrolidone) was added and mixed thoroughly to obtain a slurry with a certain viscosity; the obtained slurry was evenly coated on aluminum foil, dried at 90°C for 2 hours, and after drying, it was pressed with a tablet press, and then the pressed electrode was punched into a circular electrode sheet with a diameter of 14 mm, and placed in a vacuum drying oven at 120°C for 2 hours; in an argon-protected glove box, Celgard 2400 membrane was used as a diaphragm, a metal lithium sheet was used as a negative electrode, and 1 mol / L LiPF6 / EC+DEC+DMC (volume ratio 1:1:1) was used as an electrolyte to assemble a button battery. The assembled battery was charged and discharged above the blue electric test, the temperature was 25±1°C, and the test voltage range was 3.0~4.3V.

[0078] The test instrument for electrochemical cycle performance is the blue electric test system.

[0079] Table 1

[0080]

[0081]

[0082] According to the test results in Table 1, it can be seen that the nickel-rich ternary positive electrode material prepared by the preparation method provided by the present invention has a smoother material surface and a more uniform morphology than the comparative example, can achieve a higher specific capacity for charging and discharging at 1.0C, a higher first coulombic efficiency, and a better capacity retention rate after 100 cycles at 1.0C.

[0083] It can be seen from the test results of Examples 1 to 5 that when the preparation method, the dosage of the first lithium source, the second lithium source and the third lithium source, the lithium replenishment method, the sintering reaction conditions, and the type of lithium source are within the specified range of the present disclosure, the effect and performance of the product prepared by the present invention can be further improved.

[0084] It can be seen from the test results of Comparative Examples 1 to 3 that in Comparative Example 1, the nickel-rich precursor is not pretreated, and the lithium source is directly mixed with the nickel-rich precursor, which will lead to uneven contact between the lithium source and the nickel-rich precursor, making the single crystal material easily agglomerated during the sintering process, so that its specific capacity for charging and discharging at 1.0C is low, and the capacity retention rate of 100 cycles at 1.0C is significantly lower than that of Examples 1 to 5; since Comparative Example 2 does not perform secondary lithium supplementation before the secondary sintering, defects will occur on the surface of the material during sintering, the surface of the material is not smooth, and the morphology is uneven, so that its specific capacity for charging and discharging at 1.0C is low, the first coulomb efficiency is low, and the capacity retention rate of 100 cycles at 1.0C is significantly lower than that of Examples 1 to 5; since the amount of the third lithium source in Comparative Example 3 is not within the specified range of the present disclosure, after the secondary sintering, the residual alkali on the surface of the material will be high, thereby reducing the specific capacity of the prepared material for charging and discharging, reducing the first coulomb efficiency, and the capacity retention rate of 100 cycles at 1.0C is significantly lower than that of Examples 1 to 5.

[0085] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0086] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0087] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a nickel-rich ternary single crystal positive electrode material, wherein: The method includes: (1) contacting a mixed solution of sodium chloride, potassium chloride and a first lithium source with a nickel-rich precursor and drying; (2) mixing the nickel-rich precursor with a second lithium source and performing a first sintering to obtain a sintered material; (3) After washing and drying, the sintered material is supplemented with lithium and subjected to a second sintering; Wherein, the lithium replenishment method is wet lithium replenishment, the wet lithium replenishment uses an aqueous solution containing a third lithium source, the wet lithium replenishment method is performed by ball milling, and the ball milling time is 2 to 6 hours; The amount of the third lithium source is 1000-6000 ppm relative to the mass of the sintered material; Among them, the molar ratio of the nickel-rich precursor to the total lithium source is (1.01-1.1):1, and the total lithium source includes the first lithium source and the second lithium source; relative to 100 molar parts of the total lithium source, the amount of the first lithium source is 5-15 molar parts, and the amount of the second lithium source is 85-95 molar parts.

2. The preparation method according to claim 1, wherein The usage of the third lithium source is 4000-6000 ppm.

3. The preparation method according to claim 1, wherein In step (1), relative to the mass of the nickel-rich precursor, the mass ratio of the nickel-rich precursor to the mixed solution is (2-8):1; Wherein, the mass ratio of sodium chloride, potassium chloride, the first lithium source and water in the mixed solution is (0.5-1.5):(0.5-1.5):1:(0.5-1.5).

4. The preparation method according to claim 3, wherein The mass ratio of the nickel-rich precursor to the mixed solution is (2-6):1; The mass ratio of sodium chloride, potassium chloride, the first lithium source and water in the mixed solution is (0.9-1.2):(0.9-1.2):1:(0.9-1.2).

5. The preparation method according to claim 1, wherein The molar ratio of the nickel-rich precursor to the total lithium source is (1.01-1.08):1; The amount of the second lithium source is 90 to 95 molar parts relative to 100 molar parts of the total lithium source; The first lithium source is used in an amount of 5 to 10 molar parts relative to 100 molar parts of the total lithium source.

6. The preparation method according to claim 1, wherein The temperature of the first sintering is 450-600°C, and the holding time is 4-8 hours; the temperature of the second sintering is 810-860°C, and the holding time is 10-15 hours; the sintering is carried out in an oxygen atmosphere with an oxygen content of 90-100%.

7. The preparation method according to claim 6, wherein: The temperature of the first sintering is 500-550°C.

8. The preparation method according to claim 1, wherein The method further comprises, after the second sintering is completed, crushing and screening, wherein the particle size D50 of the screened material is 1 to 1.8 μm; Wherein, the drying temperature in step (1) is 100-180°C and the drying time is 2-6 hours; In step (3), the washing method is to use ultrapure water at 5°C according to the water-to-material ratio, the water-to-material ratio is (0.8-1.2):1, and the washing time is 8-10 minutes; the drying temperature is 100-150°C, and the time is 2-6 hours.

9. The preparation method according to claim 8, wherein: The water-to-material ratio is 1:

1.

10. The preparation method according to claim 1, wherein: The chemical formula of the nickel-rich precursor is shown in formula (I): Ni x Co y Mn z (OH)2(I), wherein 0.8≤x≤0.95, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1.

11. The preparation method according to claim 1, wherein: The first lithium source, the second lithium source and the third lithium source are the same or different and are selected from one or more of lithium hydroxide monohydrate, anhydrous lithium hydroxide, lithium carbonate, lithium acetate, lithium oxalate, lithium oxide and lithium nitrate.

12. A nickel-rich ternary single crystal positive electrode material prepared by the preparation method according to any one of claims 1 to 11, wherein: The chemical formula of the nickel-rich ternary single crystal positive electrode material is shown in formula (II): LiNi x Co y Mn z O2(II), wherein 0.8≤x≤0.95, 0.05≤y≤0.2, 0.05≤z≤0.2, x+y+z=1.

13. A lithium ion battery, wherein: Contains the nickel-rich ternary single crystal positive electrode material as described in claim 12.

Citation Information

Patent Citations

  • High-nickel ternary positive electrode material for lithium battery and preparation method of high-nickel ternary positive electrode material

    CN114804233A

  • Monocrystal ternary positive electrode material, preparation method thereof and lithium ion battery

    CN115676911A